Cognitive Improvement On School-Aged Children Through Educational Video - Livana PH; hermanto hermanto; Indras Urfiyah; Novi Indrayati (Jurnal Ilmu Keperawatan Anak, 2018)
Psychosocial development in school age is characterized by industry / productive versus low self esteem or so-called normal and distorted development. Deviant development in school age can be overcome by several actions one of which is education about the task of normal development at school age. Appropriate media in education for school-aged children with audiovisual media. Audiovisual media displays elements of images and sounds that have several functions one of which is the cognitive function which means it makes it easier for children to understand the content delivered. Research aimed to know the difference of cognitive level before and after giving video, and to know the effect of educational video to cognitive improvement of child. Research using quasy experiment design with one group pretest-posttest design. Sampling with total sampling technique on the respondent class IV until VI which amounted to 75 respondents. Results: research analysis with statistical test showed that there is influence between educational video about stage of psychosocial development toward cognitive improvement of children with median value before 54,00 and after 56,00 giving video with ρ value that is 0,00 (ρ value<0,05). Research is recommended to teachers to teach their students about the stage of psychosocial development with audiovisual media so that children can find out the tasks appropriate to the stage.